Shakespeare and the American nation - Sturgess, Kim C. (Cambridge University Press, 2004)
"Why do so many Americans celebrate Shakespeare, a long-dead English poet and playwright? By the nineteenth century newly independent America had chosen to reject the British monarchy and Parliament, class structure and traditions, yet their citizens still made William Shakespeare a naturalized American hero. Today the largest group of overseas visitors to Stratford-upon-Avon, the Royal Shakespeare Company and Bankside's Shakespeare's Globe Theatre come from America. Why? Is there more to Shakespeare's American popularity than just a love of men in doublet and hose speaking soliloquies?" "This book tells the story of America's relationship with Shakespeare: the story of how and why Shakespeare became a hero within American popular culture. Kim C. Sturgess provides evidence of a comprehensive nineteenth-century appropriation of Shakespeare to the cause of the American Nation and shows that, as America entered the twentieth century a new world power, for many Americans Shakespeare had become as American as George Washington."--Jacket